Cost of healthy and culturally acceptable diets in Brazil in 2009 and 2018 - Eliseu Verly Junior; Dayan Carvalho Ramos Salles de Oliveira; Rosely Sichieri
ABSTRACT OBJECTIVE To estimate the lowest cost of a healthy and culturally acceptable diet and to assess the evolution of its cost in the periods 2008-2009 and 2017-2018. METHODS We used data on the individual food consumption and food prices from the Pesquisas de Orçamentos Familiares (Household Budget Surveys), in the 2008-2009 and 2017-2018. The sample strata of each period were aggregated, forming 108 new strata with geographic and economic homogeneity. Linear programming models generated diets for each new stratum, considering the constraints in two models: model 1 (≥ 400g of fruits and vegetables); and model 2 (≥ 400g of fruits and vegetables, < 2300mg of sodium, sodium/potassium ratio < 1, ≥ 500mg of calcium). Each food could progressively deviate 5g from the observed consumption averages until the models found a solution in each of the strata. The objective function was to minimize the total cost of the diet. RESULTS The average observed and optimized costs were R$4.96, R$4.62 (model 1) and R$5.08 (model 2) in 2008-2009, and R$9.18, R$8.69 and R$9.87 in 2017-2018. Models 1 and 2 resulted in an increase of up to 6% and 11% in 2008-2009, and of up to 25% and 34% in 2017-2018 in the lowest income strata. The main changes observed in the two models include the reduction in the amounts of sweetened beverages, sweets, sauces, ready-to-eat foods, and an increase in fruits and vegetables, flour, and tubers. CONCLUSION The adequate amount of fruits and vegetables resulted in an increase in costs to some population strata. When the adequacy of calcium, sodium, and potassium was considered, we observed a more significant increase in cost, especially in 2017-2018.